Quality of life in palliative end-stage renal disease patients in Phra Nakhon Si Ayutthaya Hospital - Suriyabantoeng, Yanisa; Nakawiro, Pakkawee (Journal of Preventive Medicine Association of Thailand, 2020)
This descriptive research aimed to study quality of life in palliative end-stage renal disease (ESRD) patients in Phra Nakhon Si Ayutthaya Hospital. The samples were 30 palliative ESRD patients. The research instruments consisted of a questionnaire of personal characteristics and the Quality of Life Questionnaire for Chronic Kidney Disease (Kidney Disease Quality of Life Short Form: KDQOL-SFTM version 1.3) in Thai language. Data were collected from October to December 2019. Statistics used for data analysis included frequency, percentage, mean, standard deviation, median, maximum and minimum. The research results revealed that palliative ESRD patients in Phra Nakhon Si Ayutthaya Hospital had median of age (yrs.)=71.5 (Max-Min=46-93), median of renal function (eGFR)=9.05 (Max-Min=2.50–14.92), the mean of overall quality of life scores was at high level ( =70.9, SD=15.4672). In consideration of the overall quality of life of the sample as an individual, the two most frequent overall quality of life scores were in high level (33.3%), and followed by in very high level (26.7%). In conclusion, the ESRD patients can still have a good quality of life, even treated with conservative treatment without kidney replacement therapy. The findings from this research shall be utilized to jointly work among multidisciplinary to exchange experience and enhance practical knowledge in ESRD to raise the knowledge for patients and caregivers. In the policy level, the principle of palliative care in ESRD patients should be educated to the nephrology nurses so they can provide palliative care instructions and integrate the patient care between the chronic kidney disease clinic and the palliative care clinic.